(3bad GdOeGZ (B:s (3WHYI GdPcQi GdYTQjf (B: (3MQQ faSc ef GdSdhc GdhShGSj GdbgQj (B: (3WQjbI YdGL PGJj ef CQHY NWhGJ dJZjjQ cjejGA OeGZc (B/s - (3ThGQJR, LjaQjs 1951-; (3HjJj, HjaQdjs; (3GdYhjVI, SdWGf Hf ehSis; (3ThGQJR, LjaQj,s 1951-. ((3GdQjGV (B:s (3OGQ LGeYI Gdedc SYhO ddfTQ,s, 2020)
(3jYfi gPG GdcJGH HYdGL GVWQGHGJ GdhShGS GdbgQj hjQcR Ydi WQjbI YdGL PGJj aj NWhGJ CQHY JgOa dJZjjQ cjejGA GdOeGZ, hgj GdNWhGJ GdJj jOhQ MhdgG GdcJGH cdg ; hgj GdNWhI GdChdi (B: (3EYGOI GdJSejI (BRelabel (3hJYfi HEOQGc Cf GdCacGQ GdGbJMGejI gj fJjLI ddhShGS GdbgQj(B. (3hGdNWhI GdKGfjI (B: (3EYGOI GdYRh (BReattribute (3hJJVef QHW MOI GdacQI HGdhShGS GdbgQj hHGdJGdj HGNJdGd GdJhGRf GdHjhcjejGFj aj GdOeGZ hGdNWhI GdKGdKI (B: (3EYGOI GdJQcjR (BRefocus (3hJJVef GdOYhI Edi JQcjR GdGfJHGg Ydi TjA BNQ HOdG ef GdCacGQ GdhShGSjI hdh dHVY ObGFb Ch GdbjGe HSdhc BNQ(B. (3hGdNWhI GdQGHYI (B: (3EYGOI GdJbjje (BRevalue (3hJJVef EOQGc YOe CgejI acQI GdhShGS aj PGJgG eY YOe CNPgG Ydi XGgQgG(B.s
(3KHJ eUWdMGJ (B: (3UaMI (B233-246.s
(3cTGa (B: (3UaMI (B247-252.s
Keywords: (3GdYdGL GdfaSjs -- (3GdhShGS GdbgQjs -- (3GdGVWQGHGJ GdYbdjIs